Legal Reform in Political Party Financing in Nigeria: Strengthening Frameworks and Enhancing Enforcement Mechanisms - Jenigho Philip Esavwede; Peter Ikechukwu Gasiokwu; Godswill Owoche Antai (Journal of Law and Legal Reform, 2025)
Political party financing remains a critical issue in Nigeria’s democratic governance, with weak enforcement of electoral laws facilitating corruption, undue political influence, and electoral malpractice. While Nigeria possesses a robust legal framework, enforcement inefficiencies and regulatory loopholes undermine financial transparency and accountability in political processes. This paper critically examines the existing legal framework governing political party financing in Nigeria, particularly the 1999 Constitution and the Electoral Act 2022, and advocates for comprehensive reforms to enhance compliance mechanisms. Adopting a doctrinal research methodology, the paper analyses statutory provisions, judicial precedents, and international best practices to identify key areas for legal and institutional improvements. The findings reveal that effective enforcement is hindered by political interference, inadequate regulatory oversight, and outdated legal provisions. To address these challenges, this study recommends targeted reforms, including strengthening the financial disclosure obligations of political parties, increasing penalties for violations, and establishing an independent electoral finance monitoring unit within the Independent National Electoral Commission (INEC). By aligning Nigeria’s framework with global best practices, these reforms will promote greater transparency, accountability, and fairness in the country’s political finance system.